Fulvic acid – a small but powerful natural substance for agricultural and medical applications - Didiek Hadjar GOENADI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2021)
Humic substances are defined as the result of the decomposition of any organic matter, and they consist mainly of humin, humic, and fulvic acids. Compared to humin, humic acids and fulvic acid (FA) are the most explored compounds. However, FAs are less studied than humic acids because of the usually small residual quantities. Considering that its potential for bioactivity is stronger than that of humic acids, the current review was performed to evaluate the effectiveness of FA application for crops and soils and its potential as an immuno-modulator for humans. The wide application of FA is challenged by two main factors affecting the quality and the effectiveness, i.e., the type of raw material and extraction method. Lignite, low-energy coal, is the most common material for FA production besides bog, peat, and compost. Fulvic acid extraction is done through several methods, i.e., hydrogen peroxide (H2O2), alkaline (NaOH/KOH), and/or water. The latest modified method shows that the combination of H2O2 with microwave power can recover a considerable amount of FA. However, it is still difficult to apply this method for industrial scale. Due to highly specified characteristics, FA showed a great potential to improve crop performances and soil health, making it strategic for supporting sustainable agriculture in the future through biotic and abiotic stress alleviations and sustainable yield achievement, including various plantation crops and biotechnological approach. For medicinal purposes, some studies have shown highly promising results, especially as an immuno-modulator and in combating neurodegenerative disorders as well as for cancer therapy and health food fortification, which might be in line with the new paradigm so-called One Health approach. The future market of FA is also estimated to grow in a very attractive economic value. However, as data are still limited, the wide range of potential use should encourage concerted and wide research and product development efforts to achieve sustainable agriculture and human health.